Os impactos da implementação do traffic calming: estudo de caso na cidade de Jaguaribe/CE - Moreira, Ludmylla Nádja Silva (Universidade Federal Rural do Semi-Árido, 2019)
Urban planning, which does not apply moderate traffic measures to improve mobility and environmental quality in small, medium and large cities, is mostly inadequate and inefficient. In the city of Jaguaribe, territorial expansion and its consequences are noticeable, since the city presents problems in its circulation systems and inadequate quality of life and environment. For resolution purposes, soothing traffic solutions have been implemented in some major routes. This paper aims to discuss and analyze the impacts of the implementation of traffic control measures in one of the main roads of the city, a Beira Rio Avenue, marked by problems of search of programming failures. The methodology used is the documentary part, followed by the area study, the qualitative research and the data analysis, comparing the interviewees' perception about the characteristics of the research and the application of the soothing transit measures. From a perspective, through the answers of the questionnaires, it was considered as having been attributed to the volume and speed of traffic, occurrence and pregnancy of the accidents, with the increase in the probability of death, improvement in the support quality of the road and urban landscape, in addition to redeeming the use of games and landscape harmony of the area, like postcard of the city.
Keywords: Traffic calming; Mobilidade; Planejamento urbano; Mobility; Urban planning; ENGENHARIAS::ENGENHARIA CIVIL